Evaluation of candidate biomarkers to predict cancer cell sensitivity or resistance to PARP-1 inhibitor treatment - Oplustilová, L; Wolanin, K; Mistrik, M; Korinkova, G; Šimková, Dana; Bouchal, Jan; Lenobel, R; Bártková, Jiřina; Lau, A; O'Connor, M.J; Lukáš, Jiří; Bártek, Jiří (Cell Cycle, 2012)
Impaired DNA damage response pathways may create vulnerabilities of cancer cells that can be exploited therapeutically. One such selective vulnerability is the sensitivity of BRCA1- or BRCA2-defective tumors (hence defective in DNA repair by homologous recombination, HR) to inhibitors of the poly(ADP-ribose) polymerase-1 (PARP-1), an enzyme critical for repair pathways alternative to HR. While promising, treatment with PARP-1 inhibitors (PARP-1i) faces some hurdles, including (1) acquired resistance, (2) search for other sensitizing, non-BRCA1/2 cancer defects and (3) lack of biomarkers to predict response to PARP-1i. Here we addressed these issues using PARP-1i on 20 human cell lines from carcinomas of the breast, prostate, colon, pancreas and ovary. Aberrations of the Mre11-Rad50-Nbs1 (MRN) complex sensitized cancer cells to PARP-1i, while p53 status was less predictive, even in response to PARP-1i combinations with camptothecin or ionizing radiation. Furthermore, monitoring PARsylation and Rad51 foci formation as surrogate markers for PARP activity and HR, respectively, supported their candidacy for biomarkers of PARP-1i responses. As to resistance mechanisms, we confirmed the role of the multidrug resistance efflux transporters and its reversibility. More importantly, we demonstrated that shRNA lentivirus-mediated depletion of 53BP1 in human BRCA1-mutant breast cancer cells increased their resistance to PARP-1i. Given the preferential loss of 53BP1 in BRCA-defective and triple-negative breast carcinomas, our findings warrant assessment of 53BP1 among candidate predictive biomarkers of response to PARPi. Overall, this study helps characterize genetic and functional determinants of cellular responses to PARP-1i and contributes to the search for biomarkers to exploit PARP inhibitors in cancer therapy.
Keywords: záření gama; regulace genové exprese u nádorů; DNA vazebné proteiny; Drug Resistance, Neoplasm; Nuclear Proteins; DNA Damage; Poly(ADP-ribose) Polymerases; geny MDR; Female; Gamma Rays; kamptothecin; Cell Line, Tumor; ženské pohlaví; BRCA1 Protein; Neoplasms; Gene Expression Regulation, Neoplastic; Tumor Markers, Biological; Enzyme Inhibitors; lidé; Antineoplastic Agents; protinádorové látky; chemorezistence; intracelulární signální peptidy a proteiny; enzymy opravy DNA; Recombinational DNA Repair; Carcinoma; protein BRCA2; karcinom; DNA Repair Enzymes; Cell Cycle Proteins; poškození DNA; Male; protein BRCA1; inhibitory enzymů; Intracellular Signaling Peptides and Proteins; DNA-Binding Proteins; Genes, MDR; Camptothecin; proteiny buněčného cyklu; BRCA2 Protein; nádorové buněčné linie; Humans